TINJAUAN YURIDIS MENGENAI PERJANJIAN PEMBIAYAAN KULIAH DOKTER SPESIALIS PADA RUMAH SAKIT PKU MUHAMMADIYAH KABUPATEN KEBUMEN - , DYARA RADHITE ORYZA FEA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research about âA Juridicial Observation the Agreement of Funding bthe lecture of Specialist Doctor at PKU Muhammadiyah Hospital in Kebumen Regencyâ intends to know the function of notary public in the implementation of agreement the funding of lecture of specialist doctor at PKU Muhammadiyah Hospital in Kebumen Regency and to know the forms of one-achievement occur and efforts that be taken on finishing that âwanprestasiâ. The characteristic of this research is empirical judicial, that is a research that gives top priority to the field research to get the primary data and is completed the secondary data with doing literature research. This research is filed in the form of report that has characteristic descriptive analysis. It is said with descriptive because the result of this research is expected to be able to give a comprehensive and systematic illustration about a judicial observation about the implementation of agreement funding of lecture the Specialist Doctor at PKU Muhammadiyah Hospital in Kebumen Regency. It has characteristic analytical because from the result of this research is done analysis toward some aspects in law to answer set of problems in research. The result of research indicate the function of notary public in the agreement of funding the lecture of specialist doctor at PKU Muhammadiyah Hospital in Kebumen Regency has not guaranteed balance of the right and the obligation to outsiders throughout, this is caused by it is formed unilaterally without involving the notary public whether in arranging the draft of contract as at PKU Muhammadiyah Gombong. Role of the notary as a whole looks at PKU Muhammadiyah Sruweng. The form of one-achievement in the realization of agreement funding the lecture of specialist doctor at PKU Muhammadiyah Hospital in Kebumen Regency, especially at PKU Muhammadiyah Sruweng in the form of receiver of funding the lecture does not fulfill achievement at all to the outsider of giver funding the lecture, in this case the hospital. The finishing of one-achievement in implementation the agreement of funding the lecture of specialist doctor at PKU Muhammadiyah Hospital in Kebumen Regency is held by a family atmosphere.